Heat stress and potential of heat strain among solid waste collectors in Hulu Selangor Local District / Siti Rohana Mohd Yatim ... [et al.] - Mohd Yatim, Siti Rohana; Rajan, Shantakumari; Shafie, Farah Ayuni; Che Dom, Nazri; Zainudin, Nur Syuhada; Ishak, Ahmad Razali (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The aim of this study was to determine the level of heat stress and heat strain among waste collectors. The level of heat stress was measured by using environmental monitoring QUESTemp⁰36 Thermal Environment Monitor, heat stress screening checklist and questionnaire. A questionnaire known as Heat Strain Score Index (HSSI) was used to determine the heat strain index among solid waste collectors. The results of the study showed that the average environmental parameter was exceeded with the ACGIH threshold limit value of 29.5⁰C. The average humidity value was 63.43%. A chi square analysis was used to determine the p-value of HSSI. There was statistically significant differences between green zone and yellow zone of heat strain among the workers due to the p-value was less than 0.05 (p<0.05). Simple linear regression model was used to determine the relationship between heat stress exposure and heat strain score index. It can be concluded that there is no association between the heat stress exposure level and heat strain score index as proved by the statistical finding in this study.